PENGARUH AROMATERAPI INHALASI TERHADAP PENURUNAN NILAI KECEMASAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Tahan Adrianus Manalu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Aromatherapy inhalation was complemantary therapy that most effective and safe to used, the physicology problem was anxiety as the impact of chronic kidney deasese who underwent hemodialysis. The purpose of this research was to know the influence of aromatherapy inhalation on the decreased anxiety value of chronic kidney deasese who underwent hemodialysis at Grendmed Hospital Lubuk Pakam 2018. This research was quantitative research, with research design pra-experiment and used approach one group pretest–posttest. This research population of all the patient chronic kidney deasese who underwent hemodialysis at Grandmed Hospital Lubuk Pakam 2018. Sample as many 13 respodences with tecnique used purposive sampling. Statistic test used paired simple t-test with confidence level 95% (α = 0,05). The result of the research that there was influence of aromatherapy inhalation on the decreased anxiety value of chronic kidney deasese who underwent hemodialysis at Grandmed Hospital Lubuk Pakam 2018 with p value = 0,001. It is expected to the nurse to be able to apply the implamention the influence of aromatherapy inhalation on the decreased anxiety value of chronic kidney deasese who underwent hemodialysis to decrease dependency in farmacology therapy in decreasing anxiety.